2006
DOI: 10.1007/s00380-005-0901-1
|View full text |Cite
|
Sign up to set email alerts
|

The effect of early statin treatment on inflammation and cardiac events in acute coronary syndrome patients with low-density lipoprotein cholesterol

Abstract: We investigated the effects of atorvastatin on inflammation and cardiac events during the inpatient period and initial 6-month follow-up in acute coronary syndrome (ACS) patients with low low-density lipoprotein (LDL) cholesterol level. One hundred and twelve consecutive ACS patients with LDL cholesterol less than 100 mg/dl were included in the study (mean 78.2+/-12.3 mg/dl). While 70 randomly selected patients received a dose of 40 mg atorvastatin within the first 24 h on top of their standard treatment as th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(8 citation statements)
references
References 23 publications
1
6
0
1
Order By: Relevance
“…The importance of hypolipemics, especially statins, in the secondary prevention of MI has been suggested in both recent and earlier studies [22][23][24][25]. In all these studies, as in this study, the use of hypolipemics in patients after the MI as a secondary prevention measure reduced the percentage of adverse coronary events.…”
Section: Discussionsupporting
confidence: 58%
“…The importance of hypolipemics, especially statins, in the secondary prevention of MI has been suggested in both recent and earlier studies [22][23][24][25]. In all these studies, as in this study, the use of hypolipemics in patients after the MI as a secondary prevention measure reduced the percentage of adverse coronary events.…”
Section: Discussionsupporting
confidence: 58%
“… 10 But for ACS patients with low LDL-C level, statin therapy can benefit similarly. Kanadasi et al 11 found for ACS patients with a low LDL level, atorvastatin can lower the hsCRP and plasma amyloid A values on the 5th day and in the 6th month. Accordingly, Tsai et al 12 included statin therapy can significantly lower the incidence of death, reinfarction, or stroke at 6 months.…”
Section: Discussionmentioning
confidence: 94%
“…Nineteen studies documented a reduction in short-and long-term major adverse cardiovascular events after intensive treatment with statins within the first 24 hours after hospital admission for patients with ACS (LOE 1 [617][618][619][620][621][622] ; LOE 2 [623][624][625][626][627][628][629][630][631][632][633][634][635] ). Multiple studies reported consistently reduced short-term mortality and reduced incidence of death and nonfatal myocardial infarction during the 30-day follow-up with continued statin treatment or early initiation of this treatment, compared with discontinuation of statins at hospital admission of ACS patients (LOE 3 636 ; LOE 4 [637][638][639][640][641][642][643][644][645] ).…”
Section: Consensus On Sciencementioning
confidence: 99%